Selection bias, interventions and outcomes for survivors of cardiac arrest. Issue 16 (20th February 2018) - Wallace, David J; Coppler, Patrick; Callaway, Clifton; Rittenberger, Jon C; Dezfulian, Cameron; Mohan, Deepika; Toma, Catalin; Elmer, Jonathan
Abstract : Objective: Cardiac catheterisation and implantable cardioverter defibrillator (ICD) insertion are increasingly common following cardiac arrest survival. However, much of the evidence for the benefit is observational, leaving open the possibility that biased patient selection confounds the association between these invasive procedures and improved outcome. We evaluated the likelihood of selection bias in the association between cardiac catheterisation or ICD placement and outcome by measuring long-term outcomes overall and in a cause-specific approach that separated cardiac mortality from non-cardiac mortality. Methods: We performed a multivariable survival analysis of a clinical cohort between 2005 and 2013, with follow-up through 2015. We included patients who had out-of-hospital or inhospital cardiac arrest that survived to discharge, and evaluated the association between cardiac catheterisation or ICD insertion and all-cause, cardiovascular and non-cardiovascular mortality. Results: Among 678 patients who survived cardiac arrest, we observed lower all-cause mortality among patients who underwent cardiac catheterisation (adjusted HR (aHR) 0.40; P<0.01) or ICD insertion (aHR 0.55; P<0.01). However, cause-specific analysis showed that the benefits of cardiac catheterisation and ICD insertion resulted from reduced non-cardiac causes of death (cardiac catheterisation: aHR 0.24, P<0.01; ICD: aHR 0.58, P<0.01), while reduced cardiac cause of death was not associated with cardiac catheterisation (cardiac catheterisation: aHR 0.75, P=0.33). Conclusions: There is evidence of selection bias in the secondary prevention survival benefit attributable to cardiac catheterisation for patients who survive cardiac arrest. Observational studies that consider its effects on all-cause mortality likely overestimate the potential benefit of this procedure.